Forensic psychotherapy and psychological therapies in forensic mental health settings - Adshead, Gwen (Seminars in forensic psychiatry, 2024)
"Forensic psychotherapy" is a shorthand term for the treatment of offenders with psychodynamic psychotherapy. Over the last decade, a range of psychological therapies for offenders have been developed, often based on improved therapies for personality disorder. The author discusses what distinguishes forensic psychotherapy from other psychological therapies offered to offenders; and which offenders might benefit most from psychodynamically focussed therapy. The author describes how psychological treatments broadly fit within the risk needs responsivity construct and the matched stepped care system. Matched stepped care and an appropriate governance framework ensure services deliver evidence-based practices, targeting underlying needs. Clear treatment pathways exist, low- to high-intensity interventions are provided with good fidelity and the right people skills are in place to deliver these interventions. The requirement to step up in intensity and expertise level of treatment is based on a clinical formulation and risk. Having the right service in the right place at the right time delivered by the right professional is critical to reducing risk among people who are violent.